The rhetorical use of the Tibetan ergative - Tournadre, Nicolas (2024)
Tibetan as spoken in the Central province ("Lhasa dialect-) presents a standard nominal ergative structure. i.e. a specific marker for the agent2 of two-place predicates. and a 0 marker (the absolutive) for the patient of two-place predicates as well as for the only participant of one-place predicates. The ergative marker is a case particle formally identical to the instrumental. but functionally distinct from it. Besides its semantic and syntactic functions the ergative also has a rhetorical effect that will be examined below. First we will consider the standard function.